2016
DOI: 10.15196/ts560604
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes of airfares on online travel agency websites and metasearch engines, departure from Budapest

Abstract: Kulcsszavak:online utazási iroda, repülőjegyár, Budapest, metakereső oldal Tanulmányunkban a főszezoni és az előszezoni repülőjegyárak időbeli alakulását vizsgáljuk Budapest és három nyugat-európai célállomás között. Kutatásunk adatbázisának alapját az online utazási irodák és a metakereső weboldalak kínálata adta. Először egy internetes keresőmotor segítségével automatizáltuk az adatgyűjtési folyamatot, majd a lekérdezett adatokból adatbázisokat készítettünk, amelyek több mint 31 ezer repülőjegyárat tartalmaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The first is on Monday and the second is before the weekend (Thursday and Friday). This can be explained partly by the traditional mobility pattern of international tourists concentrating around the weekends and partly by international airfare policies, where the cheapest tickets can be obtained around the middle of the week (Dudás, Boros, & Vida, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The first is on Monday and the second is before the weekend (Thursday and Friday). This can be explained partly by the traditional mobility pattern of international tourists concentrating around the weekends and partly by international airfare policies, where the cheapest tickets can be obtained around the middle of the week (Dudás, Boros, & Vida, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, academic studies on concrete travel metasearch providers are rare (Dudás et al, 2017), with one exception being Edelman and Lai (2016), who analyse Google's flight metasearch in comparison with other organic and paid listings. It is proven that users who click based on relevance were clicking paid listings, whereas users influenced by page position and visuals were more likely to click on Google's flight search listing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has the power to change spatial patterns. The shortest flight data analysis (time gap) also showed that shorter travel times and lower travel considerably increase travel costs (Dudás, Boros & Vida, 2017). ).…”
Section: Literature Reviewmentioning
confidence: 99%